Contentious rituals: parading the nation in Northern Ireland - Blake, Jonathan S. (Oxford studies in culture and politics, 2019)
"In Contentious Rituals, Jonathan Blake focuses on Protestant parades in Northern Ireland to explain how and why men and women of various backgrounds choose to take part in them. Blake draws on interviews and randomized surveys with participants and non-participants and ethongraphic fieldwork at parades and related events across nine Belfast neighborhoods. He finds that partcipants are more interested in the process-oriented benefits intrinsic to the performance of the parades rather than expression of sectartian attitudes or any material incentive. They parade to express collective identity, to uphold tradition, and for the simple of pleasure of partcipiating. In fact, participants insist that their parades have nothing to do with politics at all, despite the fact that parades have sparked ethnic violence and virtually all observers consider them deeply political. Blake suggests this 'paradox of anti-politcs' helps explain the intractable nature of parading; seeing their actions as above politics allows participants to ignore or downplay the consequences"--